SISTEM KOMPUTERISASI PENGOLAHAN DATA PRAKTEK KERJA LAPANGAN (PKL) DI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS SAHID SURAKARTA - Dwi Retnoningsih; Dahlan Susilo; Hadi Pratikno (Universitas Sahid Surakarta, 2014)
The data processing system of the Job Training Informatics Engineering Program at the University of Sahid Surakarta rudimentary, especially for students who will carryout the course PKL, of course require more information about requirements, execution time, as well as the placement of the PKL is true, accurate and up to date. Looking atsome of these constraints then the authors developed a system is better to overcome some of these constraints.The data processing system made under the terms and conditions PKL registration in Informatics Engineering Program Sahid University of Surakarta. This system servesto input student data, Data lecturer, registration data PKL, and seminar PKL, and make the process of filing PKL title, appointment of supervisor, submission seminar PKL and the process of appointment of examiners PKL. The resulting output of this system in the form PKL data recap report, PKL title report, and PKL seminar report. The product resulted by this research is a tested The data processing system of the Job Training. Based on the result of system testing using McCall method with fivefactors used to assess those are : accuracy, reliability, efficiency, function, and maintenance. McCall method was chosen because it is often used and quite good toaccess the quality of software. By using McCall method this system got total score 76.60%. According to the test results required the development of a more significant toenhance the system, in order to improve the quality.